2013
DOI: 10.1101/gr.158436.113
|View full text |Cite
|
Sign up to set email alerts
|

GC skew at the 5′ and 3′ ends of human genes links R-loop formation to epigenetic regulation and transcription termination

Abstract: Strand asymmetry in the distribution of guanines and cytosines, measured by GC skew, predisposes DNA sequences toward R-loop formation upon transcription. Previous work revealed that GC skew and R-loop formation associate with a core set of unmethylated CpG island (CGI) promoters in the human genome. Here, we show that GC skew can distinguish four classes of promoters, including three types of CGI promoters, each associated with unique epigenetic and gene ontology signatures. In particular, we identify a stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
394
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(433 citation statements)
references
References 59 publications
36
394
3
Order By: Relevance
“…3B). The compiled analysis of GC skew at all CGI-associated genes oriented to the TSS and scaled to the CGI showed that whereas there is generally positive skew downstream from the TSS as previously described (Ginno et al 2013), the proximally paused genes have a sharp peak in GC skew located just downstream from the TSS and the distally paused genes have a sharp peak of GC skew at the CGI edge (Fig. 3C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3B). The compiled analysis of GC skew at all CGI-associated genes oriented to the TSS and scaled to the CGI showed that whereas there is generally positive skew downstream from the TSS as previously described (Ginno et al 2013), the proximally paused genes have a sharp peak in GC skew located just downstream from the TSS and the distally paused genes have a sharp peak of GC skew at the CGI edge (Fig. 3C).…”
Section: Resultsmentioning
confidence: 99%
“…Previous work by the Chedin group has shown a strong correlation between global GC skew, R-loop formation, and the lack of DNA methylation across CGI domains (Ginno et al 2012(Ginno et al , 2013. By use of a sequence-based algorithm, SkewR, that takes into account the degree, length, and direction of GC skew, as well as sequence composition (C + G content, CpG density), the group has classified CGIs into three classes (strong, weak, and reverse) based on a predicted propensity for R-loop formation.…”
Section: Resultsmentioning
confidence: 99%
“…CGIs represent unique chromatin environment in the genome, and are characterized by constrained divergent (bidirectional) transcription, marking by H3K4me3, and high levels of GC-skew, a sequence-based feature associated with the formation of unusual secondary structures. 35 Transcription through such regions leads to the formation of R-loops formed by the pairing of a G-rich nascent RNA to its C-rich template behind the progressing polymerase. R-loops have been suggested to play a key role in preventing DNA methylation at CGI.…”
Section: Discussionmentioning
confidence: 99%
“…35 We limited our analysis to the subset of our significantly demethylated CpGs common between the platform used here (Illumina 27K array) and that used for the TCGA samples (Illumina 450K array). This resulted in a total of 3,989 CpG sites (Resistant D 1,213, Slow D 1,527, Moderate D 906, Rapid D 342).…”
Section: Dac Induces Stable Reversal Of Cancer-specific Hypermethylationmentioning
confidence: 99%
“…In this regard, transcription through the highly GC-rich FMR1 5′ UTR region promotes (co-transcriptional) R-loop formation, 76 whereby the G-rich RNA transcript reinvades the DNA duplex and forms a stable RNA:DNA hybrid with the C-rich template strand, thereby displacing the non-template DNA strand. Although R-loop formation normally occurs at multiple loci throughout the genome, 81 defects in mRNA processing can result in an Rloop-dependent activation of the DNA damage response and lead to the accumulation of the phosphorylated H2A variant, γH2AX, which is associated with the DNA damage repair process. 82,83 We have recently reported R-loop formation both at the endogenous FMR1 locus and in an inducible episomal system in which the expanded CGG-repeat (~95 CGG) is located upstream of a GFP reporter.…”
Section: R-loop Formation/dna Damage Responsementioning
confidence: 99%